2005
DOI: 10.1152/ajpendo.00095.2005
|View full text |Cite
|
Sign up to set email alerts
|

Determination of triglyceride in the human myocardium by magnetic resonance spectroscopy: reproducibility and sensitivity of the method

Abstract: -The primary aim of this investigation was to determine the reliability and sensitivity of 1 H magnetic resonance spectroscopy ( 1 H-MRS) as a method for quantifying myocardial triglyceride (TG) content in humans over time and in response to metabolic perturbations. Three separate experiments were designed to quantify myocardial TG content 1) over a 90-day period, 2) after a high-fat meal, and 3) after a 48-h fast. Proton spectra were collected from a 10 ϫ 20 ϫ 30-mm 3 voxel placed within the intraventricular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
125
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(135 citation statements)
references
References 25 publications
10
125
0
Order By: Relevance
“…Due to substrate competition [9], systemic and myocardial GU rates were low; the latter was inversely correlated with the increment in 3-OHB and NEFA levels. An increase in myocardial palmitate esterification and content was observed in the fasting group compared with the other groups, a finding consistent with studies in healthy and type 2 diabetic individuals [2,15,35]. These studies reported an increased myocardial TG content when lipolysis was induced by caloric restriction or a 48 h fasting period, unless acipimox was coadministered to counteract increasing NEFA levels [12].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Due to substrate competition [9], systemic and myocardial GU rates were low; the latter was inversely correlated with the increment in 3-OHB and NEFA levels. An increase in myocardial palmitate esterification and content was observed in the fasting group compared with the other groups, a finding consistent with studies in healthy and type 2 diabetic individuals [2,15,35]. These studies reported an increased myocardial TG content when lipolysis was induced by caloric restriction or a 48 h fasting period, unless acipimox was coadministered to counteract increasing NEFA levels [12].…”
Section: Discussionsupporting
confidence: 86%
“…Work in fasting dogs has demonstrated that elevated plasma NEFA concentrations, achieved by intralipid-heparin infusion, were associated with greater content and synthesis rates of myocardial TG compared with conditions with lower plasma NEFA, such as insulin or saline infusion [36]. In contrast, high-fat feeding does not change myocardial TG content in healthy subjects, despite notable increases in plasma TG and NEFA levels and an accumulation of liver fat [16,35]. Notably, insulin concentrations are low during caloric restriction or intralipid administration, while a high insulin in response to a high-fat diet may limit myocardial TG accumulation by suppressing the release of NEFA from adipose tissue and TG from the liver, which is consistent with our findings.…”
Section: Discussionmentioning
confidence: 99%
“…17,[19][20][21][22] Previous studies have shown that diabetic obese humans and rodents have elevated hepatic, myocellular and myocardial lipid content, and that treatment with pioglitazone leads to decreased hepatic and myocardial lipid together with improved insulin sensitivity. 23 Assessment of EF volume (EFV) and myocardial TG content (MTGC) has already been validated [24][25][26] with the emergence of non-invasive three-dimensional volumetric imaging techniques such as 3-T magnetic resonance imaging (MRI). This technique is also useful to address the relationship between excess myocardial lipids and impaired myocardial function.…”
Section: Introductionmentioning
confidence: 99%
“…Although a limit-based error analysis of the relaxation correction has been published [37], many studies report CV's based only on repeated acquisitions and do not include the uncertainty of the T 2 correction [5,8,9,12]. For species with comparatively long T 2 's, such as brain metabolites, the additional uncertainty is minor.…”
Section: Relaxationmentioning
confidence: 99%
“…Localized magnetic resonance spectroscopy (LMRS), which uses gradient-enabled imaging systems, is increasingly used both in basic and clinical assays including qualitative and quantitative compositional, temperature, and pH measurements [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. Kreiss [16] summarized the main aspects of LMRS, including spectral artifacts, systematic errors, and general criteria for ensuring spectral quality.…”
Section: Introductionmentioning
confidence: 99%